The Effectiveness of Forensic Medicine in the Investigation of Murder and Harassment at the Cirebon City Police - Ubaiyadi, Sallsa Nabila Dewi; Yuningsih, Maylafasya Ratna; Yuniarni, Ervina; Henda, Rd.; Nurhaqi, Ari (PT FORMOSA CENDEKIA GLOBAL, 2025)
The importance of forensic medicine in supporting the criminal investigation process, especially in cases of murder and harassment. In some cases, conventional evidence is not enough to reveal the facts that occurred, so a scientific approach is needed through the analysis of biological, medical, and toxicological evidence, the use of forensic medicine often faces various challenges in its application, such as objections from the victim regarding autopsy. For this reason, it is necessary to know the extent of the effectiveness of forensic medicine in handling the crime of murder and harassment, as well as the challenges faced by investigators in the case at the Cirebon City Police. This type of research is normative juridical, examining theories, concepts, legal principles, and laws and regulations. Data collection techniques include interviews and document studies. The results of the study show that forensic medicine is very effective in helping to solve murder cases at the Cirebon City Police. However, in the case of verbal harassment, it is still difficult to prove because there is no trace of the perpetrator on the victim's body, so in this case, the doctor can only make a medical certificate regarding the victim's psychological state.